Pemanfaatan Website Wizer Me untuk Mengembangkan E-LKPD Interaktif Bagi Guru Sekolah Dasar. - Sobri, Muhammad; Fauzi, Asri; Rahmatih, Aisa Nikmah; Indraswati, Dyah; Amrullah, Lalu Wira Zain (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
The ability to develop interactive student worksheets is a competency that educators really need to support the learning process in the classroom. To improve teacher competence, it is necessary to conduct training in using free websites to develop interactive e-LKPD. One of the website platforms that can be used by teachers is the wizer me website. The platform is easy to use and the features provided in preparing the e-LKPD are very complete. The method of implementing community service is carried out in several stages, namely: the preparation stage, the implementation stage, and the evaluation stage. The target of this service is SDN 26 Mataram teachers, totaling 14 teachers. The results of this service can be said to be successful, seen from the teacher's enthusiasm in the practice of making interactive e-LKPD with materials prepared by the service team. Besides that, the teacher's enthusiasm in this training can be seen from the increase in the teacher's test results on the ability to understand the material delivered by the service team. The types of questions practiced by the teacher in making e-LKPD using the wizer me website are multiple choice, short entries, descriptions, matching, searching for words, sorting, labeling pictures. Therefore, by increasing teacher competence in compiling interactive e-LKPD, it is hoped that teachers can develop more fully using the teacher's own materials and ideas according to the needs and characteristics of students.